Methodology For Organizing The Effectiveness Of Choir Conductor’s Activity - Muzafarova Saodat Khaydarovna (Genius Publishing Group, 2025)
The article analyzes methodological approaches that ensure the effectiveness of a choir conductor’s activity. It shows that the conductor’s personal qualities, professional training, and pedagogical mastery directly affect the productivity of choral rehearsals. Factors such as criteria for repertoire selection, systematic organization of rehearsals, creation of a psychological atmosphere within the choir, and the use of innovative technologies are highlighted. In addition, the role of aesthetic education and the development of creative collaboration in choral performance is substantiated
Keywords: choral art; choir conductor; methodology